Influence of Cleft lip and Palate on Characteristics of Hearing Loss - Jadranka Handzic (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Objectives: To find out and evaluate and compare hearing threshold of the cleft-side vs. non-cleft side in children with unilateral cleft lip and palate (UCLP), to find out if the severity of the morphological and functional changes on the cleft lip and palate side correlate with severity of the hearing loss, to find out if ears of cleft vs.non cleft side show difference in improvement of the hearing loss with aging. Method: Tympanometry and pure tone audiometry performed in study group of 76 children with UCLP of the left side and median age of 6 years. All of the children previously have undergone operatively repaired left cleft lip and palate under the standard conditions. Tested children have long term history of hearing loss and no ear surgery. Results of tonal audiometry were evaluated for speech frequencies (500Hz, 1000Hz, 2000Hz and 4000 Hz) according to age subgroups of 1-3, 4-7, and 8-12 years. Hearing loss was considered of mild, moderate or severe level. Ears of the non-cleft side with no morphological structural defect, served as control in the evaluation of the hearing thresholds of the ears of cleft side. Results: Highest average of hearing loss across speech frequencies showed youngest age group of 1-3 year. There was no difference between levels of hearing loss between cleft and non-cleft side. At the age of 4-7 yr. cleft side ears showed highest hearing loss average and medians for separate frequencies, if compared with non/cleft side ears. Cleft side ears showed higher incidence of ears with moderate and severe hearing loss which do not improve hearing threshold with aging. Increase of ears with normal hearing is not significant with aging. Ears on cleft side showed mild level ears. Ears of non-cleft side ears showed increase of ears with normal and mild hearing loss with aging. Conclusion: Ears of cleft side ears in unilateral cleft lip and palate children are more pronounced for hearing loss and have less improvement of hearing threshold with aging, because of negative influence  of structural defects in the region of the Eustachian tube of the of cleft lip and palate side.